Integrated bioinformatics identifies key mediators in cytokine storm and tissue remodeling during Vibrio mimicus infection in yellow catfish (Pelteobagrus fulvidraco) - Feng, Yang; Wang, Jiao; Fan, Wei; Geng, Yi; Huang, Xiaoli; Ouyang, Ping; Chen, Defang; Guo, Hongrui; Deng, Huidan; Lai, Weimin; Zuo, Zhicai (Frontiers in Immunology, 2023)
The pathogenesis of Vibrio mimicus infection in yellow catfish (Pelteobagrus fulvidraco) remains poorly understood, particularly regarding the impact of infection with the pathogen on primary target organs such as the skin and muscle. In this study, we aimed to comprehensively analyze the infection mechanism of V. mimicus using integrated bioinformatics based on a 1/10 LC50 seven-day post-infection. Our histopathological examination revealed significant pathological changes in the skin and muscle, characterized by necrosis and inflammation. Moreover, tissue remodeling occurred, with perimysium degeneration and lesion invasion into the muscle along the endomysium, accompanied by a transformation of type I collagen into a mixture of type I and type III collagens in the perimysium and muscle bundles. Our eukaryotic transcriptomic and 4D label-free analyses demonstrated a predominantly immune pathway response in both the skin and muscle, with downregulation observed in several cell signaling pathways that focused on focal adhesion-dominated cell signaling pathways. The upregulated genes included interleukins (IL)-1 and -6, chemokines, and matrix metallopeptidases (mmp)-9 and -13, while several genes were significantly downregulated, including col1a and col1a1a. Further analysis revealed that these pathways were differentially regulated, with mmp-9 and mmp-13 acting as the potential core regulators of cytokine and tissue remodeling pathways. Upregulation of NF-κB1 and FOSL-1 induced by IL-17C and Nox 1/2-based NADPH oxidase may have held matrix metallopeptidase and cytokine-related genes. We confirmed these relevant regulatory pathways by qPCR and ELISA in expanded samples. Our findings provide new insights into the complex immune response to V. mimicus infection in yellow catfish, highlighting potential targets for developing therapies.